1998
DOI: 10.1007/s004970050142
|View full text |Cite
|
Sign up to set email alerts
|

MEI1 , an Arabidopsis gene required for male meiosis: isolation and characterization

Abstract: The T-DNA tagged mutant gene of Arabidopsis thaliana, mei1, produces after meiosis an abnormal tetrad, consisting of five to eight microspores of varying sizes and DNA contents. Plant DNA flanking the inserted T-DNA was isolated by inverse PCR. An approximately 16-kb DNA fragment spanning the T-DNA insertion site was isolated by screening a wild-type genomic library, using the plant flanking DNA as a probe. Using RT-PCR and RNA isolated from very young flower buds, a cDNA fragment was obtained. Nucleotide sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…This alignment supports the conclusion that like other ORC subunits, ORC6 is conserved in plants. Interestingly, our analysis indicates that the ORC6 C terminus is conserved Kosugi and Ohashi (2002);32, Toueille et al (2002);33, Castillo et al (2003); 34, Raynaud et al (2006);35, Furukawa et al (2003);36, Furukawa et al (2001);37, Jenik et al (2005); 38, Ronceret et al (2005); 39, He and Mascarenhas (1998);40, Yang and Sheila (2002); 41, Grelon et al (2003);42, Ishibashi et al (2001);43, Marwedel et al (2003);44, Ishibashi et al (2005); 45, Ishibashi et al (2006);46, Xia et al (2006); 47, Kimura et al (2003); 48, Kimura et al (2000b);49, Taylor et al (1998);50, Sunderland et al (2004); 51, Bonatto et al (2005); 52, Sunderland et al (2006).…”
Section: Preinitiationmentioning
confidence: 61%
“…This alignment supports the conclusion that like other ORC subunits, ORC6 is conserved in plants. Interestingly, our analysis indicates that the ORC6 C terminus is conserved Kosugi and Ohashi (2002);32, Toueille et al (2002);33, Castillo et al (2003); 34, Raynaud et al (2006);35, Furukawa et al (2003);36, Furukawa et al (2001);37, Jenik et al (2005); 38, Ronceret et al (2005); 39, He and Mascarenhas (1998);40, Yang and Sheila (2002); 41, Grelon et al (2003);42, Ishibashi et al (2001);43, Marwedel et al (2003);44, Ishibashi et al (2005); 45, Ishibashi et al (2006);46, Xia et al (2006); 47, Kimura et al (2003); 48, Kimura et al (2000b);49, Taylor et al (1998);50, Sunderland et al (2004); 51, Bonatto et al (2005); 52, Sunderland et al (2006).…”
Section: Preinitiationmentioning
confidence: 61%
“…It has been reported that the Arabidopsis meiotic gene MEI1 (He and Mascarenhas 1998) contains introns that do not follow the GU...AG rule for intron splicing (Brown et al 1996). However, when the splice sites in ASY1 were examined all 21 introns were found to obey the rule, hence it is likely that the discrepancy is due to the software used to predict potential ORFs.…”
Section: Discussionmentioning
confidence: 98%
“…In Arabidopsis, the QTL on chromosome 1 in the Ler 3 Cvi population included the MEI1 gene (He and Mascarenhas 1998;Grelon et al 2003). A 9-kb region surrounding the gene MEI1 was sequenced in three distinct Arabidopsis lines (Col, Ler, and Cvi).…”
Section: Distribution Of Crossover Eventsmentioning
confidence: 99%